Knowledge transfer from european multinational corporations to their subsidiaries in China: contextual perspectives and expatriate's roles - Jincheng, Wang (2014)
This study aims to explore the factors impeding the knowledge transfer from European multinational corporations’ (MNC) headquarters to their subsidiaries in China. And the roles that the expatriates play in the process of knowledge transfer are also examined. A quantitative research method is adopted in this study. We collected 67 questionnaires in total responded by the European expatriates in China. The results indicate that the expatriates actively participate in a wide range of knowledge transfer areas and that seven factors related to various contexts are identified by the expatriates as the primary causes of the difficulties in the process of knowledge transfer. The analysis of the results, which is related to the overall contexts in China, is also presented. We conclude the study with the limitations and suggestions for future research.